You can also write that as
y = x log 6
to find the inverse swap the x and the y, and solve for y:
x = y log 6
y = x/log 6
2006-12-28 02:20:48
·
answer #1
·
answered by Jim Burnell 6
·
1⤊
0⤋
Inverse is the sequence of operations that "un-does" y.
Strategy is to solve for x as a function of y, then have x and y switch places.
y=xlog6
y/log6=x
So, the inverse of y = y(inv)=x/log6
2006-12-28 10:42:39
·
answer #2
·
answered by Jerry P 6
·
0⤊
0⤋
y=log 6^x
y=x log 6
x=y/ log 6
2006-12-28 16:05:33
·
answer #3
·
answered by yupchagee 7
·
0⤊
0⤋
y = log(6^x)
x = log(6^y)
x = ylog(6)
x/y = log(6)
y/x = 1/(log(6))
y = x/(log(6))
ANS : y^-1 = x/log(6)
2006-12-28 11:51:05
·
answer #4
·
answered by Sherman81 6
·
0⤊
0⤋
y=log6^x
i.e. y = xlog6
hence 1/y=1/(xlog6)
2006-12-28 10:25:19
·
answer #5
·
answered by yoovraj s 2
·
0⤊
0⤋
y=xlog6
x=y/log6
y^(-1)=x/log6
2006-12-28 11:43:49
·
answer #6
·
answered by Maths Rocks 4
·
0⤊
0⤋